The Correlation of Heat Tolerance Coefficient (HTC) and Temperature Humidity Index (THI) with Milk Production of Dairy Cows in Bangun Lestari Farm, Tulungagung - Rachmawati, Achadiah; Taufiq, Muhammad Ni’am; Arif, Ani Atul (CV. Komunitas Dunia Peternakan, 2024)
Determining the relationship between environmental adaptability and milk production across various parities using HTC and THI values was the aim of this study. Purposive sampling was employed to choose thirty dairy cows of parity 1 and 2, for the study. For this investigation, a case study was employed. The temperatures and humidity of the barn environment were used to measure the THI value, which was determined by the HTC value, the milk production of mothers with varying parities, and the rectal temperature and respiratory frequency. Research results demonstrated a negative connection between the two independent variables—the THI and HTC values—and milk production at parities 1 and 2. This suggests that either environmental stressors or higher HTC or THI values resulted in lower milk production. At parity 1, there was a poor correlation, and at parity 2, a moderate correlation between the HTC value and milk production. The correlation coefficients for parity 1 and parity 2 were, respectively, r = 0.410, R2 = 0.168, and r = 0.370, R2 = 0.137. There was just a slight association observed between the THI value and milk production at parities 1 and 2. The correlation coefficient for parity 1 was (r = 0.220; R2 = 0.049), but the correlation coefficient for parity 2 was (r = 0.227; R2 = 0.51). According to the study's findings, milk production in parities 1 and 2 is only marginally correlated with HTC and THI values.